2015
DOI: 10.1007/s11626-015-9939-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the chemical and liver extract-induced hepatic differentiation of adipose derived stem cells

Abstract: Adipose-derived stem cells (ADSCs) have been put forward as promising therapeutics for end-stage liver disease (ESLD). In the present study, we compared the effects of defined chemicals and liver extract on the hepatic differentiation of ADSCs. ADSCs were isolated according to the method described in our previously published study. Subsequently, the differentiation of ADSCs was induced separately by chemicals (including hepatic growth factor (HGF), fibroblast growth factor (FGF), and oncostatin M (OSM)) and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Serum from rats that underwent 70% partial hepatectomy (PH) promoted the hepatogenic differentiation of ADMSCs in vitro by upregulating the secretion of IL-6 and HGF [61]. In addition, ADMSCs exhibited more rapid changes in cellular morphology and expressed higher levels of AFP and ALB after incubation with liver extract than after culture in the presence of chemicals including HGF, fibroblast growth factor (FGF), and oncostatin M [62]. Trichostatin A, a specific histone deacetylase inhibitor, significantly enhanced the hepatogenic differentiation of ADMSCs by upregulating the expression of miR-122, ALB, HNF4α, and HNF6 while downregulating the AFP level [63].…”
Section: Introductionmentioning
confidence: 99%
“…Serum from rats that underwent 70% partial hepatectomy (PH) promoted the hepatogenic differentiation of ADMSCs in vitro by upregulating the secretion of IL-6 and HGF [61]. In addition, ADMSCs exhibited more rapid changes in cellular morphology and expressed higher levels of AFP and ALB after incubation with liver extract than after culture in the presence of chemicals including HGF, fibroblast growth factor (FGF), and oncostatin M [62]. Trichostatin A, a specific histone deacetylase inhibitor, significantly enhanced the hepatogenic differentiation of ADMSCs by upregulating the expression of miR-122, ALB, HNF4α, and HNF6 while downregulating the AFP level [63].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Sellaro et al [11] demonstrated that porcine-liver-derived powder maintained primary hepatocyte function in vitro at levels comparable to Matrigel, considered the most helpful substitute to maintain hepatic cells biological features in vitro. Concerning this, it has recently been proposed that liver extracts can modulate the hepatocyte differentiation of At-MSCs, suggesting an interplay between hepatic tissue and MSCs [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although our data do not provide information regarding the components of the LLP responsible for these effects, recent contributions from the literature, in addition to vitamins, minerals, and other bioactive molecules, emphasize the presence in liver tissue of more complex multi-molecular particles, such as exosomes and microvesicles capable of controlling and stimulating the metabolic activity of the organ both in physiological and pathological conditions [45,46]. Interestingly, it has been observed that exosomes derived from liver cells modulate various biological activities (such as control of cell proliferation and apoptosis, regulation of gene transcription) on cultured hepatocytes [47] and other cell types [43]. Furthermore, the maintenance of hepatocytespecific functions of primary cultures expanded in the presence of liver extracellular matrix [11,42] has been observed, suggesting that that liver tissue extracts can support in vitro hepatocyte culture and could be considered a candidate for the development of treatment for liver diseases [42].…”
Section: Discussionmentioning
confidence: 99%
“…This laboratory succeeded to differentiate MSCs into adipocytes, osteoblasts, chondrocytes, cardiomyocytes, insulin-producing cells, and neuron-like cells [36][37][38][39]. Moreover, various animal models of different diseases were also developed in order to execute pre-clinical trials [32,37,40]. The animal disease models treated by stem cell transplantation have included femoral head necrosis, type 1 and 2 diabetes mellitus [32], bone marrow failure, injured knee cartilage [41], aged skin, liver cirrhosis [37], hindlimb ischemia [42,43], heart failure [44], and spinal cord injury [45].…”
Section: Stem Cell Milestone In Viet Nammentioning
confidence: 99%